Reading comprehension and its relationship with working memory capacity when reading horizontally scrolling text. Issue 9 (September 2018) - Harvey, Hannah; Walker, Robin
The horizontally scrolling format, where text is presented in a single line drifting right to left, is relatively commonly used to display text on digital screens. This format presents a potentially challenging reading situation as the text must be followed smoothly to the left (to track individual words) while rightward eye movements are made as usual to progress through the text. This conflict may reduce attention allocated to upcoming text. Returning to previously encountered text is also more difficult with this format. Here, a sustained reading comprehension task was used to compare performance with horizontally scrolling and multi-line static text formats. Results showed that literal comprehension can be reasonably well maintained with scrolling text, although small decrements are seen at faster scrolling rates. However, they indicated that this format makes it more difficult to answer questions requiring an inference to be made. The contribution of working memory capacity and the impact of display speed on these effects were considered. These findings have implications for the application of this format in digital media and also more widely for the conditions required for successful in-depth reading comprehension with any text format.